2018
DOI: 10.5334/pb.409
|View full text |Cite
|
Sign up to set email alerts
|

The Delicate Balance to Adjustment: A Qualitative Approach of Student’s Transition to the First Year at University

Abstract: First year experience in higher education has been extensively investigated in the literature. Yet, two limitations can be identified out of the literature. The majority of the studies focused on single factor analysis, restraining the multifactorial understanding of adjustment’s determinants. Moreover, the temporal unfolding of the first year at the university has mainly been disregarded, limiting the dynamic framing of adjustment process. To overcome these limitations, the current study used a longitudinal q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 56 publications
3
28
0
4
Order By: Relevance
“…De Clercq et al (2018) suggested the importance of career guidance from the start, with not only long-term goals but also concrete and clear information about study. They suggested the importance of generating opportunities in experiencing study regularly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Clercq et al (2018) suggested the importance of career guidance from the start, with not only long-term goals but also concrete and clear information about study. They suggested the importance of generating opportunities in experiencing study regularly.…”
Section: Discussionmentioning
confidence: 99%
“…The Nicholson transition cycles model (see Coertjens et al 2017;De Clercq et al 2018) describes the transition to higher education through four phases, namely preparation, encounter, adjustment and stabilisation. The preparation phase concerns students' orientation on and preparation for higher education, and usually takes place well before students have registered for a course at university.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CIT, developed as an interview method ( Chell, 2004 ), is recognized as an effective exploratory tool to collect self-reported experiences of essential real-life events ( Butterfield et al, 2005 ). According to Flanagan (1954) , a critical incident is a crucial event that makes a significant contribution—positively or negatively—to a certain phenomenon. In the present study, the basics of CIT were used to explore events that students perceived to be essential for their lived first-year academic experience during the first semester of their FYHE.…”
Section: Methodsmentioning
confidence: 99%
“…To classify the reported text segments into relevant themes (RQ1), a cross-case content analysis was undertaken ( Krippendorff, 2004 ). In the first phase of this analysis, conforming to the CIT literature, we adopted an inductive open-coding approach to make a first abstraction of the critical incidents ( Flanagan, 1954 ; Chell, 2004 ). For each of the reported critical incidents, the entire text segment was allocated to one or more pertaining codes, which resulted in a transparent overview of the data.…”
Section: Methodsmentioning
confidence: 99%